A Survey on Trust-based Intrusion Detection for Version Number Attack on RPL - Patel, Hiral; Patel, Hiren; Shrimali, Bela (International Journal of Computer Sciences and Engineering, 2025)
The IoT incorporates the network of physical devices (things) that are connected to the global Internet for transferring and performing computation in lager application area. Routing protocols are designed for Low Power and Lossy network (RPL) to support communication in the constrained network with thousands of such power-scarce nodes in IoT. Consequently, due to the increases in millions and billions of connected devices in the constraint network(s) all over the world, security has become the aspect of most significance. Lightweight Intrusion Detection System (IDS) is required to examine the malicious activity and malicious node in the network of IoT, to filter out different attacks in a resource-constrained environment. In this paper, the lightweight trust based intrusion detection methods covering the different attacks of the wireless sensor network and IoT are reviewed and discussed. This article may give the direction to the beginners to identify appropriate methods and observations for their future research in the application domain of IoT.